TRPC6 is a Biomarker for Prognosis and Immunotherapy of Stomach Adenocarcinoma Based on Bioinformatic Analysis and Experimental Validation - Hu X; Wang H; Sun H; Zhang J; Ye Z; Huang Z (ImmunoTargets and Therapy)
Xingchi Hu,1,2 Hongwei Wang,1,2 Haitao Sun,3 Jingxin Zhang,3 ZhenXiong Ye,4 Zhenhua Huang3 1Department of General Surgery, Yancheng First Hospital, Affiliated Hospital of Nanjing University Medical School, Yancheng, Jiangsu, 224000, People’s Republic of China; 2Department of General Surgery, The First People’s Hospital of Yancheng, Yancheng, Jiangsu, 224000, People’s Republic of China; 3Department of General Surgery, The Affiliated People’s Hospital of Jiangsu University, Zhenjiang, Jiangsu, 212002, People’s Republic of China; 4Department of General Surgery, Yangpu Hospital, Tongji University School of Medicine, Shanghai, 200090, People’s Republic of ChinaCorrespondence: Xingchi Hu, Department of General Surgery, Yancheng First Hospital, Affiliated Hospital of Nanjing University Medical School, Yancheng, Jiangsu, 224000, People’s Republic of China, Email xingchihu@163.com Zhenhua Huang Department of General Surgery, The Affiliated People’s Hospital of Jiangsu University, Zhenjiang, Jiangsu, 212002, People’s Republic of China, Email zhenhuahuangzj@163.comBackground: Transient receptor potential canonical 6 (TRPC6), a key member of the TRPC family, is involved in diverse physiological and pathological processes. Although previous studies have implicated TRPC6 in the progression of stomach adenocarcinoma (STAD), its precise functions and mechanisms remain unclear. Understanding TRPC6’s role in STAD may provide insights into its prognostic and therapeutic potential.Methods: Using transcriptional and clinical data from The Cancer Genome Atlas (TCGA) database, we assessed the expression and prognostic value of TRPC6 in STAD through Kaplan-Meier survival curve analysis and correlation studies. Immune-related parameters, including immune cell infiltration and immune checkpoint gene expression, were also evaluated. Additionally, drug response analyses explored TRPC6’s association with therapeutic agents. In vitro experiments were conducted to investigate TRPC6’s role in STAD cell proliferation, migration, and invasion, focusing on its regulation of the PI3K-Akt signaling pathway.Results: TRPC6 was significantly overexpressed in STAD tissues compared to normal tissues, with high TRPC6 expression associated with poor overall survival. TRPC6 expression correlated strongly with immune cell infiltration, immune checkpoint genes, and sensitivity to therapies such as Lapatinib, anti-CTLA4, and anti-PD1 treatments. Functional assays confirmed that TRPC6 promotes STAD cell proliferation, migration, and invasion by activating the PI3K-Akt signaling pathway.Conclusion: This study highlights the prognostic significance of TRPC6 in STAD and its potential as a therapeutic target. TRPC6’s involvement in immune regulation and cancer cell progression underscores its dual role in STAD pathogenesis and treatment, offering new avenues for targeted therapy development.Keywords: TRPC6, stomach adenocarcinoma, immunotherapy, biomarkers